Prokrastinasi akademik remaja penggemar k-pop di Indonesia - Ramdhani, Rina Nurhudi; Boreel, Monica Surya Lestari (Universitas Mathla'ul Anwar Banten, 2023)
Many young K-Pop fans are very active in using social media so that it is indicated that it will trigger academic procrastination behavior. This study aims to find out the general description of academic procrastination in young Indonesian K-Pop fans. This study uses a quantitative research design. The subjects of this study were 400 young K-Pop fans (388 girls and 12 boys). The technique of determining the sample using nonprobability sampling technique with purposive sampling method. In this study, data measurement used the academic procrastination questionnaire which measures academic procrastination in the area of academic procrastination and the reasons for doing academic procrastination. The results showed that the picture of academic procrastination in young Indonesian K-Pop fans was in the moderate category. The results of this study are expected to provide insight and become a reference in designing guidance and counseling services to reduce academic procrastination.